The impact of E-Journals on the Malaysian scholarly community - Roosfa, H.; Mohd Yahya, M.A. (2011)
Electronic journals are a new scenario for the Malaysian scholarly community. Thus, this paper presents the positive and negative impacts of the scenario. Currently, Malaysian universities are competing with each other to be in the list of top ranked world universities. To achieve the target, academicians are under pressure to become visible by publishing their works in journals indexed by various international databases. Hence, publishing research findings in e-journals has become compulsory among the Malaysian academics. The aim of this study is to identify the. impact of electronic journals on the Malaysian scholarly community. Policies implemented by Malaysian. universities pertaining to the rules for publishing works in electronic journals were studied. In addition, this study focuses on the impact of electronic journals on the academician career path, promotional exercise and rewards received by Malaysian scholars. The study includes input and responses by leaders of the Academician Association and directors and editors of university presses.